UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA VOCABULARY STICKING GAME PADA SISWA KELAS I SD - Sumi Resminawati; Arsyi Rizqia Amalia; Rifky Aditya Ramadhan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early reading skills are the foundation for elementary school students to succeed in learning every subject. Based on the results of observations in class I SDITech Al-Fawwaz, it was found that some students still had difficulty recognizing letters, reading syllables, composing words, and reading simple sentences. This study aims to explain the application of Vocabulary Sticking Game media and determine its effect on improving students' early reading skills. The study used the Classroom Action Research (CAR) method of the Kemmis and McTaggart model which consists of two cycles, namely planning, implementation, observation, and reflection. The research subjects were 22 students of class I SDITech Al-Fawwaz. Data collection techniques used tests, observation, and documentation. The results showed that the application of Vocabulary Sticking Game media was able to improve students' early reading skills. Student learning completeness increased from 54% in Cycle I to 63% in Cycle II. Thus, Vocabulary Sticking Game media can be used as an alternative learning media to improve elementary school students' early reading skills.